THE INFLUENCE OF VILLAGE ASSISTANCE FUNDS ON PRODUCTION, PRODUCTION COSTS AND FARMERS' INCOME : Case Study: Kuta Bale Village, Tigapanah District, Karo Regency, North Sumatra Province - Medi Lilis Wenny Nainggolan (Journal of Agriculture, 2022)
This study aims to determine the mechanism of development proposals to analyze the differences before and after the Village Fund Allocation to production costs, production, and farmers' income in the research area. The method of determining the area is done purposively. The method of determining the research sample is the census method by interviewing 32 sample farmers. The data collected are primary data and secondary data. The data analysis method was carried out using the one-sided average difference test using the Paired Sample T-test on SPSS. Based on the results of the study, it was found that (1) the development proposal was carried out by deliberation between the village apparatus and the village community, and (2) there was a significant difference in the production of chilli and tomato plants after the village assistance fund, (3) there was a significant difference in the cost of farming production chilli and tomatoes after the village assistance fund, (4) There is a significant difference in the income of chilli and tomato farmers after the village fund assistance.